2023
DOI: 10.1038/s41598-023-49767-x
|View full text |Cite
|
Sign up to set email alerts
|

TWAS revealed significant causal loci for milk production and its composition in Murrah buffaloes

Supriya Chhotaray,
Vikas Vohra,
Vishakha Uttam
et al.

Abstract: Milk yield is the most complex trait in dairy animals, and mapping all causal variants even with smallest effect sizes has been difficult with the genome-wide association study (GWAS) sample sizes available in geographical regions with small livestock holdings such as Indian sub-continent. However, Transcriptome-wide association studies (TWAS) could serve as an alternate for fine mapping of expression quantitative trait loci (eQTLs). This is a maiden attempt to identify milk production and its composition rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Similarly, Cai et al [ 13 ] discovered several TWAS genes as candidates for important economic traits in Simmental beef cattle, including NADSYN1 , NDUFS3 , LTF , and KIFC2 in the liver, GRAMD1C , TMTC2 , and ZNF613 in backfat, as well as TIGAR , NDUFS3 , and L3HYPDH in muscle. Chhotaray et al [ 14 ] reported some causal loci related to milk production and composition traits in Murrah buffaloes. These findings emphasize the potential of TWAS in uncovering genes underlying complex traits, making it crucial for unraveling the genetic basis of milk production traits in buffalo populations and ultimately addressing the limitations encountered by previous GWAS.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Cai et al [ 13 ] discovered several TWAS genes as candidates for important economic traits in Simmental beef cattle, including NADSYN1 , NDUFS3 , LTF , and KIFC2 in the liver, GRAMD1C , TMTC2 , and ZNF613 in backfat, as well as TIGAR , NDUFS3 , and L3HYPDH in muscle. Chhotaray et al [ 14 ] reported some causal loci related to milk production and composition traits in Murrah buffaloes. These findings emphasize the potential of TWAS in uncovering genes underlying complex traits, making it crucial for unraveling the genetic basis of milk production traits in buffalo populations and ultimately addressing the limitations encountered by previous GWAS.…”
Section: Introductionmentioning
confidence: 99%